Monitoring and Detection System of Level and Turbidity in Embankment Water in Real Time Based on IoT - Alamsyah, Hendri; Sawaludin, Prengki; Kalsum, Toibah Umi (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
In 2020 there were floods in the Air Hitam and Tanjung Alam villages, Bengkulu Province, and surrounding areas. These floods have caused a lot of losses to the community, especially resulting in damage to houses and agricultural land. Flooding in the Air Hitam and Tanjung Alam village areas, Bengkulu Province, occurred due to heavy rain that fell for 3 consecutive days, resulting in the overflow of the Musi Hydroelectric Power Plant (Hydroelectric Power Plant) dam which was unable to withstand the water discharge and eventually overflowed. So in this research, a prototype system for monitoring and detecting height and turbidity in embankment water in real time based on IoT will be designed. The method used is a waterfall, where the ultrasonic sensor and turbidity sensor will be connected to the ESP-8266 NodeMCU so that data on the height and turbidity of the embankment water is obtained in real-time via the user interface on the Thinger io Platform. Apart from that, the system uses LEDs in red, yellow, and green as indicators of the embankment water level. These results show that the implementation of a real-time IoT-based monitoring and detection system for height and turbidity in embankment water has good capabilities. This is indicated by the user being able to see data on the prototype system for monitoring and detecting height and turbidity in embankment water in real-time based on IoT with the display of numbers and LED indicator lights. The seawater height scale used in the system on the red LED indicator lights is 16 - 20 cm, yellow is 10 - 15 cm, and green is 0 - 9 cm.